2007
DOI: 10.1177/1368430207074730
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Importance of Information: The Effects of Mentioning Information, Shared Information Bias, Ownership Bias, Reiteration, and Confirmation Bias

Abstract: Participants were given information for and against the decriminalization of marijuana and discussed the issue in groups. Factors affecting rated importance of information after the group discussion were examined. Participants did not rate information that was mentioned during the discussion as more important than information not mentioned, and participants did not rate shared information they mentioned as more important than unshared information. Participants did rate shared information other group members me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 58 publications
4
33
1
Order By: Relevance
“…Our proposition is in line with other recent studies suggesting that the failure of groups to solve hidden profiles may not only be a function of problems with group interaction, but also due to individual-level processes (see also Klocke, 2007;van Swol, 2007). Of course, this does not mean to say that we deny the existence of hindering group-level processes.…”
Section: Implications and Future Directionssupporting
confidence: 78%
See 1 more Smart Citation
“…Our proposition is in line with other recent studies suggesting that the failure of groups to solve hidden profiles may not only be a function of problems with group interaction, but also due to individual-level processes (see also Klocke, 2007;van Swol, 2007). Of course, this does not mean to say that we deny the existence of hindering group-level processes.…”
Section: Implications and Future Directionssupporting
confidence: 78%
“…However, research suggests that the individual preference effect also operates in interacting groups, since preference-inconsistent information is devalued by group members interacting face-to-face (Klocke, 2007;Mojzisch et al, 2008;Toma & Butera, 2009;van Swol, 2007). Moreover, it has been shown that even if an advocacy group decision procedure is applied that precludes members from prematurely aggregating their preferences and that leads to more comprehensive information pooling, group decisions are not improved in hidden profile situations (Greitemeyer et al, 2006), which could be due to the individual preference effect.…”
Section: Limitationsmentioning
confidence: 99%
“…Again, preference-consistent items were evaluated as more important than preference-inconsistent items. Although Van Swol (2007) did not confound preference consistency and ownership, the data are still equivocal. Note that preferenceconsistent items are introduced and repeated in discussions more often than preference-inconsistent items (e.g., Dennis, 1996;Klocke, 2007;Schulz-Hardt, Brodbeck, Mojzisch, Kerschreiter, & Frey, 2006).…”
Section: Empirical Evidence For the Three Evaluation Biasesmentioning
confidence: 82%
“…Three studies have focused on the ownership bias (Chernyshenko, Miner, Baumann, & Sniezek, 2003;Van Swol et al, 2003;Van Swol, 2007). In each study, participants discussed a decision case face-to-face.…”
Section: Empirical Evidence For the Three Evaluation Biasesmentioning
confidence: 99%
See 1 more Smart Citation